2016
DOI: 10.1021/acs.analchem.6b02553
|View full text |Cite
|
Sign up to set email alerts
|

Adductomics Pipeline for Untargeted Analysis of Modifications to Cys34 of Human Serum Albumin

Abstract: An important but understudied class of human exposures is comprised of reactive electrophiles that cannot be measured in vivo because they are short lived. An avenue for assessing these meaningful exposures focuses on adducts from reactions with nucleophilic loci of blood proteins, particularly Cys34 of human serum albumin, which is the dominant scavenger of reactive electrophiles in serum. We developed an untargeted analytical scheme and bioinformatics pipeline for detecting, quantitating and annotating Cys34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(229 citation statements)
references
References 34 publications
12
217
0
Order By: Relevance
“…This method is analogous to that used by Grigoryan et al, who quantified HSA adducts, modified at Cys34, in tryptic digests relative to a ‘housekeeping peptide’, which was also derived from HSA. Using synthetic standards, the authors showed that the peak area ratios (Cys34 adduct/housekeeping peptide) were highly linear over a wide dynamic range of adduct concentrations (Grigoryan et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…This method is analogous to that used by Grigoryan et al, who quantified HSA adducts, modified at Cys34, in tryptic digests relative to a ‘housekeeping peptide’, which was also derived from HSA. Using synthetic standards, the authors showed that the peak area ratios (Cys34 adduct/housekeeping peptide) were highly linear over a wide dynamic range of adduct concentrations (Grigoryan et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…The elucidation of the binding sites of xenobiotics to proteins is useful for the elucidation of the potential immunogenic properties of the adduct 92 or to develop strategies to measure multiple adducts after isolating a peptide of Alb with a nucleophilic hot-spot such as Cys34. 6,93,94 …”
Section: Generation Of Reactive Metabolites and Identification Of Promentioning
confidence: 99%
“…Recently, a rapid method was developed to obtain about 0.1 mg of Alb with a 72–75% purity. 94 Plasma (5 μL) was added to 60 μL of 50% methanol and incubated at room temperature for 15 min with constant agitation. The samples were centrifuged to remove precipitates and immediately diluted with four volumes of digestion buffer, and digested with trypsin.…”
Section: Albumin Purification and Hydrolysis Conditions For Adduct Stmentioning
confidence: 99%
See 2 more Smart Citations